2013
DOI: 10.1021/ma402334t
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable N3-Substituted Imidazolium-Based Alkaline Anion Exchange Membranes: Experimental Studies and Theoretical Calculations

Abstract: Imidazolium cations with various N3-substituents (including methyl, butyl, heptyl, dodecyl, isopropyl, and diphenylmethyl groups) were synthesized and investigated in terms of their alkaline stability. The effect of the N3-substituent on the alkaline stability was studied by quantitative 1H NMR spectra and density functional theory (GGA-BLYP) calculations. The isopropyl substituted imidazolium cation ([DMIIm]+) with the highest LUMO energy value exhibited the highest alkaline stability in aqueous NaOH. The [DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
144
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 75 publications
3
144
0
2
Order By: Relevance
“…Some of the alkyl-substituted 1,2-dimethylimidazolium cations (1,2-DMIms) have also been synthesized and evaluated in alkaline solution. [11] The alkaline stability of imidazolium cations observed in experiments (DMIIm…”
Section: Substituent Effect On Lumo Energymentioning
confidence: 99%
“…Some of the alkyl-substituted 1,2-dimethylimidazolium cations (1,2-DMIms) have also been synthesized and evaluated in alkaline solution. [11] The alkaline stability of imidazolium cations observed in experiments (DMIIm…”
Section: Substituent Effect On Lumo Energymentioning
confidence: 99%
“…14, However, it has been shown that quaternary ammonium-based AEMs are sensitive toward Hofmann elimination 20,41 and direct nucleophilic elimination reactions 42,43 that result in loss of ion exchange capacity (IEC) and ionic conductivity. To resolve the stability problem inherent to quaternary-ammonium-group-containing AEMs, several alternative cations, including imidazolium, 41,44,45 benzimidazolium, 3,45,46 guanidinium, 15,47,48 phosphonium 8,9,49 and metal cations 50,51 have been proposed and investigated. Phosphonium-based AEMs were investigated by Gu et al 52 Gu et al attached benzyl-tris(2,4,6-trimethoxyphenyl) phosphonium (TTMPP + ) onto polysulfone backbone to make AEMs, and found them to be alkaline stable; There was no ionic conductivity fade after immersion in 1M KOH for 30 days at room temperature.…”
mentioning
confidence: 99%
“…• C. [17][18][19][20][21] However, the AEMs with excep- * Electrochemical Society Active Member. a Present address: Institute for Molecular Engineering, University of Chicago, Chicago, Illinois 60637, USA.…”
mentioning
confidence: 99%